The Influence of Awareness and Knowledge on Taxpayer Compliance in Paying Taxes According to PP No. 55 Of 2022 on MSMEs in Garut District - Nurlaela, Lina; Ningsih, Winda (Fakultas Ekonomi Universitas Garut, 2023)
The aim of this research is to identify and test the impact of taxpayer awareness and knowledge on the level of taxpayer compliance in making tax payments in accordance with PP Regulation No. 55 of 2022 on Micro, Small and Medium Enterprises (MSMEs) in Garut Regency. Primary data is the data used in this research and this research is quantitative. The Garut Pratama Tax Service Office (KPP) is the focus of the research as well as the population in the research. Random technique (random sampling) is a technique used in sampling through questionnaires. In taking samples, the calculations used the Slovin formula, and 100 respondents were successfully selected. This research provides results that partially taxpayer awareness and knowledge positively influences taxpayer compliance in paying taxes in accordance with Government Regulation Number 55 of 2022 for Garut Regency MSMEs. Then taxpayer compliance in making tax payments is influenced simultaneously by the taxpayer's knowledge and awareness in accordance with Government Regulation No. 55 of 2022 on MSMEs.